Desenvolvimento de Fios de Microfibrilas de Celulose em Matriz de Alginato para Confecção de Placas Balísticas - Mulin, Lucas Braga (2024)
Due to the versatility of applications and the need for environmentally friendlier products, nanocellulosic materials (CNM) emerge as an option. In this context, the present study aimed to produce a CNM fiber using an alginate matrix for use in the manufacturing of ballistic plates. Fibers with an alginate matrix reinforced with microfibrillated cellulose (MFC), cellulose nanocrystals (CNC), and both together were produced at different concentrations. These were characterized through Fouriertransform infrared spectroscopy (FTIR), thermogravimetry (TG), X-ray diffraction (XRD), density, water absorption, scanning electron microscopy (SEM), and tensile mechanical testing. The fiber with a 4.5% concentration of MFC was selected for the production of composites, serving as reinforcement in an epoxy matrix at concentrations of 0, 10, 20, and 30%. These composites were qualified through FTIR, TG, XRD, SEM, flexural and tensile mechanical testing, Charpy impact testing, and ballistic testing. The C30 composite was considered the best option as it absorbed the highest amount of energy without shattering, making it capable of absorbing multiple shots.